Radial Distribution Network Topology Optimization Using Genetic Algorithms Considering Uncertain Load and Distributed Generation - Ribeiro, Vitor Hugo (2015)
This paper aims to study distribution network topology optimization considering uncertain load and distributed generation. Gradual increase of distributed generation in distribution network leads the network operator companies to concern more about having the best network topology, so their costs can be the lowest. MATLABTM genetic algorithms function is used to model this mathematical problem in its basic definition. A stochastic multi-objective programming algorithm is implemented and a decision maker applied to choose the best solution of non-dominated solutions set found.